Ask Question
19 February, 03:30

Write the equation of the function g (x) if g (x) = f (x - 3) + 1 and f (x) = x3 + 1.

+3
Answers (1)
  1. 19 February, 04:03
    0
    We can find the value of f (x-3) by putting x-3 in place of x in f (x)

    therefore,

    f (x-3) = (x-3) 3 + 1

    by putting the value of f (x-3) in g (x)

    g (x) = (x-3) 3 + 1 + 1

    = (x-3) 3 + 2
Know the Answer?
Not Sure About the Answer?
Find an answer to your question 👍 “Write the equation of the function g (x) if g (x) = f (x - 3) + 1 and f (x) = x3 + 1. ...” in 📗 Mathematics if the answers seem to be not correct or there’s no answer. Try a smart search to find answers to similar questions.
Search for Other Answers